Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

girleegurl

  • 3 years ago

3x+2y=19 3x+3y=-6 solve the simultaneous equation by using elimination method.

  • This Question is Closed
  1. Butterfly16
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    3x+2y=19 3x+3y=-6--> Multiply by -1: 3x+2y=19 -1(3x+3y=-6) 3x+2y=19 -3x-3y=6 ----------- -1y=25 y= -25 Now, plug it back into the first equation: 3x+2(-25)=19 3x-50=19 3x=69 x=23 x=23, y= -25 Does it make sense? :o)

  2. Chlorophyll
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    @girleegurl In this case should you add or subtract using elimination method?

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy